Pengaruh Kemampuan Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Badan Pendapatan Daerah Kabupaten Sikka - Marliana Ervani Weni; Walter Obon; Viktor Eko Transilvanus (Jurnal CUAN Universitas Nusa Nipa Maumere, 2023)
This research is grounded on the issue of the achievement of performance that has not reached the specified target. This research aimed to (1) determine the description of employee performance, workability, and workmotivation; (2). analyse the work ability and motivation on employee performance at the Regional Revenue Agency of Sikka Regency both simultaneouslyor partial. The population in this research were employees who worked at the Regional Revenue Agency of Sikka Regency as many as 57 people. Due to limited population, this research was carried out by census or saturated sampling. Data were collected through questionnaires and analysed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing done through the F test and t test. The results of the description analysis showed that the variables of employee performance, work ability, and work motivation were categorized as good. The results of the test statistics showed that the variables of work ability and work motivation had a positive and significant effect on employee performance partially. The results of the F tes statistics showed that the variables of work ability and work motivation had a significant effect on employee simultaneously. The determination analysis result reveald that the two independent variablesin this study were able to explain the fluctuation of the employee performance at Regional Revenue Agency of Sikka Regency by 38.7